Hot corrosion behavior of superalloy IN718 at 550 and 650 C - Mahobia G.S.; Paulose N.; Singh V. (My University, 2025)
This investigation was undertaken to evaluate oxidation and hot corrosion behavior of the Fe-Ni-based superalloy IN718, at 550 and 650 C, to explore its performance as turbine engine components under marine environment. Uncoated and different salt-coated samples (100 wt.% NaCl, 75 wt.% Na2SO 4 + 25 wt.% NaCl, and 90 wt.% Na2SO4 + 5 wt.% NaCl + 5 wt.% V2O5) were exposed in air at 550 and 650 C under cyclic heating and cooling for 100 h. Weight gain was studied for both uncoated and salt-coated samples. X-ray diffraction, scanning electron microscopy, and electron dispersive spectroscopy were used to characterize the oxidation and corrosion products. A possible mechanism of corrosion, based on the corrosion compounds, is discussed. The variation in weight gain with time showed a parabolic growth of oxides. Coating with NaCl was found to be detrimental both at 550 C as well as 650 C. On the other hand, the salt mixture of NaCl and Na2SO4 had no effect at 550 C; however, it was detrimental at higher temperature of 650 C. Coatings of salt mixture of Na 2SO4, NaCl, and V2O5 caused very slow oxidation at both the temperatures. Increase in thickness of salt coating was observed to enhance the rate of hot corrosion. Among the three types of salt coatings, the coating of NaCl was found to be most damaging both at 550 and 650 C. © 2013 ASM International.